Evaluasi Instalasi Kelistrikan Sesuai Standar Puil di CV Multi Teknik Perkasa Palembang - Riko Saputra; M. Saleh Al Amin; Yudi Irwansi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Research conducted at CV Multi Teknik Perkasa Palembang indicates that the total installed power for various panels is 18,448 watts, consisting of 448 watts for lighting panels, 5100 watts for induction motor power panels, 9000 watts for cooling panels, and 3900 watts for lamp and socket panels. Further analysis reveals that the power consumption does not exceed the available power. Therefore, the electrical installation at CV Multi Teknik Perkasa Palembang is in good and safe condition for use.